دور مؤسسات التنشئة الاجتماعية في حماية وتعزيز الأمن المجتمعي - مرجة شيماء (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
تهتم هذه الدراسة بتوضيح دور مؤسسات التنشئة الاجتماعية في حماية وتعزيز الأمن المجتمعي في ظل التغيرات الراهنة، خاصة مع ظهور مواقع التواصل الاجتماعي ووسائل الإعلام التي أصبحت جزء لا يتجزأ من حياة الأفراد وفرضت نفسها على اتجاهات وسلوكيات المجتمع وأثرت في أنماطهم الثقافية والفكرية. وعلى هذا الأساس تم طرح إشكالية مساهمة مؤسسات التنشئة الاجتماعية في حماية وتعزيز الأمن المجتمعي، وقد تم اعتماد المنهج الوصفي من أجل الإجابة على الإشكالية المطروحة، وخلصت الدراسة إلى نتيجة مفادها أن مؤسسات التنشئة الاجتماعية تعتبر من أهم الأساليب والآليات التي يمكن الاعتماد عليها لحماية الأمن المجتمعي وتعزيزه، حيث أنها تتفق كلها على الدور الذي تؤديه كل من الأسرة والمدرسة والمجتمع المدني في تحقيق الأمن المجتمعي للدول . Abstract: This study attempts to clarify the role of socialization institutions in protecting and enhancing social security in light of the current changes, especially with the emergence of social networking sites and the media, which have become an integral part of the lives of individuals and imposed themselves on the trends and behaviors of society and influenced their cultural and intellectual patterns. On this basis, the problem of socialization institutions in protecting and enhancing community security was raised, and the descriptive approach was adopted in order to answer the problem posed, and the study concluded that socialization institutions are considered one of the most important methods and mechanisms that can be relied upon to protect and enhance social security, as they all agree on the role played by the family, school and civil society in achieving societal security for countries.